Factors Influencing Fashion Adoption among the Youth in Johannesburg, South Africa - Venter, Marike; Chinomona, Richard; Chuchu, Tinashe (Journal of Economics and Behavioral Studies, 2016)
Fashion in Africa has undergone a tremendous transformation process due to an increase in international trade. As a result, African consumerism has surfaced. Through being part of the global community, the youth in Africa capitalizes on the wide variety of fashions available, and they view fashion as a medium for expressing their identity. More specifically, in South Africa, fashion is used as the ideal vehicle for the youth to re-map previously fixed racial identities. Although a number of studies have explored this subject in an array of contexts, limited research has focused on factors that drive fashion adoption among the youth in Johannesburg. In view of this identified research gap, the present study aims to investigate the impact of fashion consciousness, the need for uniqueness, interpersonal influence, individualism/collectivism, and masculinity/femininity on fashion adoption. A Field study was conducted in Johannesburg and research data were collected from 400 respondents aged between 18 to 29 years. Linear regression analysis was performed to explore the relationship between the quantitative outcome variable and the predictor variables of the study by use of the SPSS 22 and the AMOS 22 software program. The results reveal that two of the five variables positively influence fashion adoption, while individualism/collectivism has an inverse relationship with fashion adoption. The significance of gaining insight into such factors, draw from the rich political history of South Africa and how the youth’s conflicting identities may influence the modern concept of adopting global fashion trends.